When nudges aren't enough: Incentives and habit formation in public transport usage - Christina Gravert; Linus Olsson Collentine (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
In three large-scale field experiments with over 32,000 individuals, we investigate whether public transport uptake can be in uenced by behavioral interventions and by economic incentives. Despite their effectiveness in other domains, we find a tightly estimated zero for social norms and implementation intentions on ridership. Doubling the trial period from two to four weeks significantly increases uptake and long-term usage. This increase is sustained for months after removing the incentive. The effect is mainly driven by initial low users, which is evidence for habit formation. While there is scope for long-term behavior change, nudges might not be the right approach.
Keywords: C93; D04; D91; L91; 330; transport; nudging; field experiment; habit formation